2020
DOI: 10.1186/s13287-020-01990-3
|View full text |Cite
|
Sign up to set email alerts
|

si-SNHG5-FOXF2 inhibits TGF-β1-induced fibrosis in human primary endometrial stromal cells by the Wnt/β-catenin signalling pathway

Abstract: Background Intrauterine adhesions (IUAs) are manifestations of endometrial fibrosis characterized by inflammation and fibrinogen aggregation in the extracellular matrix (ECM). The available therapeutic interventions for IUA are insufficiently effective in the clinical setting for postoperative adhesion recurrence and infertility problems. In this study, we investigated whether si-SNHG5-FOXF2 can serve as a molecular mechanism for the inhibition of IUA fibrosis ex vivo. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(19 citation statements)
references
References 47 publications
0
19
0
Order By: Relevance
“…Whether other cytokines are involved in the regulation has not been further studied. Another study showed that lncRNA-SNHG5 regulates Wnt/β-catenin by targeting FOXF2 and participates in fibrosis ( Liu et al, 2020c ). This experiment verified that lncRNA-SNHG5 is highly expressed in the IUA cell model and positively regulates FOXF2, which verified that silencing lncRNA-SNHG5 could effectively block the Wnt/β-catenin pathway and inhibit the process of fibrosis.…”
Section: Role Of Ncrnas In the Pathophysiology Of Intrauterine Adhesionmentioning
confidence: 99%
“…Whether other cytokines are involved in the regulation has not been further studied. Another study showed that lncRNA-SNHG5 regulates Wnt/β-catenin by targeting FOXF2 and participates in fibrosis ( Liu et al, 2020c ). This experiment verified that lncRNA-SNHG5 is highly expressed in the IUA cell model and positively regulates FOXF2, which verified that silencing lncRNA-SNHG5 could effectively block the Wnt/β-catenin pathway and inhibit the process of fibrosis.…”
Section: Role Of Ncrnas In the Pathophysiology Of Intrauterine Adhesionmentioning
confidence: 99%
“…Previously, Wnt signaling has been reported to contribute to stem cell aging and increase tissue fibrosis [ 25 ]. Other reports have also indicated the role of Wnt signaling in the ECM formation in the endometrium [ 26 ], which may also contribute to fibrosis formation. Thus, it is possible that the pathogenesis of IUA is partially due to hyper-activation of Wnt signaling, which leads to increased growth of the fibrotic tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has been reported that the aberrantly activated Wnt/β-catenin pathway was confirmed to stimulate TGF-β-mediated fibrosis and mediate fibrogenesis in the endometrium ( 65 , 66 ). FOXF2 protein, which activated Wnt/β-catenin pathway and upregulated Collagen Type V Alpha 2 (COL5A2) transcription in the endometrium, was reported to promote fibrogenesis in the IUA as well ( 67 , 68 ). Therefore, the interaction between many proteins or signaling pathways is of significance to the pathogenesis of IUA.…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, these signaling pathways not only were functional in promoting angiogenesis, but also exerted therapeutic effects via other mechanisms. For instance, Wnt/β-catenin pathway promoted angiogenesis, and was involved in TGF-β1-mediated fibrosis ( 67 , 142 ). Therefore, further researches need to characterize the role of pathways in ameliorating IUA by MSC-EVs.…”
Section: Methodsmentioning
confidence: 99%